2010
DOI: 10.1007/s10534-010-9374-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological responses and programmed cell death induced by cadmium in Genipa americana L. (Rubiaceae)

Abstract: Cadmium (Cd) originating from atmospheric deposits, from industrial residues and from the application of phosphate fertilizers may accumulate in high concentrations in soil, water and food, thus becoming highly toxic to plants, animals and human beings. Once accumulated in an organism, Cd discharges and sets off a sequence of biochemical reactions and morphophysiological changes which may cause cell death in several tissues and organs. In order to test the hypothesis that Cd interferes in the metabolism of G. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 30 publications
2
27
0
4
Order By: Relevance
“…Structural changes in the chloroplasts of the progeny more susceptible ('Catongo' Â 'Catongo') to stress by metals was probably due to increased ROS, as evidenced by severe damages in the structures of chloroplasts, particularly in thylakoid membranes and the granum (Paramonova et al, 2003). The same was observed in the structure of leaf chloroplasts of Genipa americana subjected to toxicity by Cd (Souza et al, 2011). Furthermore, a study by Daud et al (2009) involving Gossypium hirsutum cultivars (BR001 and GK30) has found ultra-structural changes resulting from increasing Cd concentrations, as for example the higher number of nucleoli.…”
Section: Stressmentioning
confidence: 68%
See 1 more Smart Citation
“…Structural changes in the chloroplasts of the progeny more susceptible ('Catongo' Â 'Catongo') to stress by metals was probably due to increased ROS, as evidenced by severe damages in the structures of chloroplasts, particularly in thylakoid membranes and the granum (Paramonova et al, 2003). The same was observed in the structure of leaf chloroplasts of Genipa americana subjected to toxicity by Cd (Souza et al, 2011). Furthermore, a study by Daud et al (2009) involving Gossypium hirsutum cultivars (BR001 and GK30) has found ultra-structural changes resulting from increasing Cd concentrations, as for example the higher number of nucleoli.…”
Section: Stressmentioning
confidence: 68%
“…As these treatments were selected because Souza et al (2011) in a study of phytotoxicity by Cd, found that the other doses used in this study do not cause changes to the tissue level. Immediately after collection, the plant material was fixed in 3% glutaraldehyde (Merck, Germany) and sodium cacodylate (Merck, Germany) buffer 0.1 M, pH 6.9, for 4 h. Then the samples were transferred to 50% alcohol (Merck, Germany) and stored at 4°C in refrigerator.…”
Section: Plant Anatomymentioning
confidence: 99%
“…Based on the results of light microscopy work with D. carota, Corguinha et al (2012) proposed that Cd affects plant growth in two separate phases, with the first phase impacting the functional and cytological events (1-4 days of Cd exposure), and the second phase impacting cell to cell separation, cell hypertrophy, and thiol-peptide content (4-14 days of Cd exposure). Cadmium is also known to inhibit photosynthesis by a variety of means including: reducing the transcription of genes which are related photosynthesis such as rbcL, psaB and psbA (Qian et al 2010); inactivating Rubisco and phosphoenol pyruvate carboxylase (Bashir et al 2013); inducing lipid peroxidation (Iannone et al 2010), interfering with protochlorophyllide production (Prasad 2004), reducing the activity of enzymes involved in CO 2 fixation and inhibiting chlorophyll biosynthesis (Stobart et al 1985); enhancing proteolysis (Pena et al 2007); interfering with leaf transpiration through changes in stomatal conductance and stomatal density (Souza et al 2011;Baryla et al 2001) and; disturbing nutrient metabolism and plant antioxidant machinery (Gill and Tuteja 2010). For B. napus, Cd application has also been found to reduce the concentration of leaf pigments, including lutein, neoxanthin, β-carotene and violaxanthin (Baryla et al 2001).…”
Section: Effects Of CD On Seed Germination and Plant Growthmentioning
confidence: 99%
“…Increase in transpiration rate with increasing cadmium is happening because the stomata remain open and this leads to a decrease in stomatal resistance (Benavides et al, 2005). Cadmium damages chloroplast thylakoid membranes and by inhibiting activity of Calvin cycle enzymes such as Rubisco, and electron transport chain and damaging stomatal cells results in stomatal opening and consequently increases the transpiration (Souza et al, 2011). Vermicompost in addition to the increasing population and activity of beneficial microorganisms in the soil provides nutrients and water needed for the plant, increases the stomatal resistance, and reduces the amount of transpiration (Ortíz-Castro et al, 2009).…”
Section: Results and Discussion Leaf Electrolyte Leakagementioning
confidence: 99%
“…Cadmium exists in contaminated soils as free ions, which easily dissolve in water. Once it accumulates in an organism, cadmium discharges and sets off a chain of biochemical reactions and morpho-physiological changes which may cause cell death in several tissues and organs (Souza et al, 2011). Retarded growth of plants through the effect on meristematic cell division and plant growth regulation has been reported as a cadmium toxicity symptom (Arancon et al, 2004).…”
Section: Introductionmentioning
confidence: 99%